Validation of a simplified medication adherence questionnaire in a large cohort of HIV-infected patients: the GEEMA Study - Hernando Knobel; Jordi Alonso; José L. Casado; Julio Collazos; Juan Martino González; Isabel Ruiz‐Camps; José María Kindelán; Alexia Carmona; Javier Juega; Antonio Ocampo (2002)
Objective To assess the effectiveness of the simplified medication adherence questionnaire (SMAQ) in identifying non-adherent patients. Design Prospective observational study of adherence. The six-item SMAQ was developed. The following aspects were evaluated: (i) criterion validity, comparison with electronic adherence monitoring; (ii) construct validity, association between adherence, as defined by the SMAQ, and virological outcomes; and (iii) reliability, internal consistency and reproducibility. Patients A group of 3004 unselected HIV patients who had initiated nelfinavir therapy combined with other antiretroviral drugs [21% naive, 15% protease inhibitor (PI)-naive, 64% PI-experienced] between January 1998 and December 1999 were enrolled in 69 hospitals in Spain. The SMAQ was administered at months 3, 6 and 12. Results The SMAQ showed 72% sensitivity, 91% specificity and a likelihood ratio of 7.94 to identified non-adherent patients, compared with the medication-event monitoring system (40 patients evaluated). At month 12, 1797 patients were evaluated, of whom 32.3% were defined as non-adherent; viral load < 500 copies/ml found in 68.3% of the adherent, and 46% of the non-adherent patients. A logistic regression analysis of PI-naive patients was performed, including age, sex, baseline viral load > 5 log10/ml, CD4 cell count < 200 × 106/l, and non-adherence as independent variables. Non-adherence was the only significant risk factor in failing to achieve virological suppression. Cronbach's alpha internal consistency coefficient was 0.75, and overall inter-observer agreement was 88.2%. Conclusion The SMAQ appears to be an adequate instrument with which to assess adherence in HIV-infected patients, and may be applied in most clinical settings.